Epicardial fat and coronary artery disease: Role of cardiac imaging. (March 2021) - Guglielmo, Marco; Lin, Andrew; Dey, Damini; Baggiano, Andrea; Fusini, Laura; Muscogiuri, Giuseppe; Pontone, Gianluca
Abstract: Epicardial adipose tissue (EAT) represents the fat depot located between the myocardium and the visceral pericardial layer. Far from being an inert tissue, EAT has been recognized as secreting a large amount of bioactive molecules called adipokines, which have numerous exocrine and paracrine effects. Recent evidence demonstrates that pericoronary adipose tissue (PCAT) – the EAT directly surrounding the coronary arteries – has a complex bidirectional interaction with the underlying vascular wall. While in normal conditions this mutual cross-talk helps maintain the homeostasis of the vascular wall, dysfunctional PCAT produces deleterious pro-inflammatory adipokines involved in atherogenesis. Importantly, PCAT inflammation has been associated with coronary artery disease (CAD) and major cardiovascular events. This review aims to provide an overview of the imaging techniques used to assess EAT, with a specific focus on cardiac computed tomography (CCT), which has become the key modality in this field. In contrast to echocardiography and cardiac magnetic resonance (CMR), CCT is not only able to visualize and precisely quantify EAT, but also to assess the coronary arteries and the PCAT simultaneously. In recent years, several papers have shown the utility of using CCT-derived PCAT attenuation as a surrogate measure of coronary inflammation. This noninvasive imaging biomarker may potentially be used to monitor patient responses to new antinflammatory drugs for the treatment of CAD. Graphical abstract: Image 1 Highlights: - Adversely remodelled and dysfunctional epicardial adipose tissue (EAT) secretes proinflammatory. adipokines which can promote atherogenesis in the coronary arteries. - EAT volume can be assessed with multimodality imaging (echo, CMR and cardiac CT) and associates with CAD and MACE. - Coronary CT angiography is the only modality able to simultaneously assess the coronary arteries and pericoronary adipose tissue (PCAT). - PCAT attenuation quantified from CCTA is an imaging biomarker of coronary inflammation associated with CAD and MACE. - PCAT attenuation may potentially be used to monitor the response to antinflammatory agents.